Creative Economic Empowerment Tulip Dasawisma Group, Sukorejo Village Through Environmentally Friendly Ecoprint Art Skills - Rahayuningsih, Margareta; Widowati, Widowati; Karsinah, Karsinah; Alighiri, Dante; Suwarti, Suwarti (Universitas Negeri Semarang, 2025)
The Dasawisma (Dawis) “Tulip” Family Welfare Empowerment (PKK) Group of RT 13 RW 05 Sukorejo Village need a featured product that can be developed into a pioneering Micro Small Medium Enterprise (MSME/ UMKM). Ecoprint has the potential to be a featured product because the materials are available around the Dawis environment, such as Yellow trumpet tree (tabebuya), Jamaica cherry (kersen), Mahogany, Tropical almond (ketapang), and Cosmos (kenikir). The leaves and bark of these plants can be used as ecoprint materials and natural dyes. On this basis, two solutions are offered: 1) increasing the knowledge of the Dawis members in developing eco-friendly ecoprint, 2) increasing the skills of the Dawis members in making ecoprint as a pioneer to create a business unit. These can be achieved through the introduction of eco-friendly ecoprint, increasing the capacity of skills through training and mentoring, as well as monitoring and evaluation of ecoprint products as a pioneering business unit. The results of community service show that: 1) increased knowledge of Dasawisma group members about ecoprint, 2) an increase in ecoprint-making skills of Dasawisma Tulip members, 3) produced hijab, pashmina, and clutch products. The outputs achieved are 1) news in electronic mass media, 2) copyright on ecoprint making procedures, 3) publication of activity videos, and 5) journal publications that are in the process of being submitted. This community service activity is in line with SDGs 4 (Quality Education) and SDGs 9 (Industry, Innovation, and Infrastructure).